Hydroponic pepper growing on baked clay pellets - Szilágyi, Z.; Slezák, K.; Ferenczy, A.; Terbe, I. (International Journal of Horticultural Science, 2006)
Nowadays one of the most important issues of greenhouse vegetable production in soilless media is the protection of the environment, in particular, the selection of the root medium to be applied. The objective of the trial was to test the applicability of baked (expanded) clay granules in hydroponic pepper growing with special respect to the growing pot (plastic tubes and buckets with bottom and lateral holes). From the result of the experiment it can be concluded that baked clay pellets, similarly to rockwool, are a suitable medium for providing root anchorage for pepper, however, it is necessary to examine some technological issues (e.g. fertilization, irrigation) prior to starting a large scale commercial cultivation. Relative to the three growing containers tested, it can be concluded that with the 4-8 mm crushed clay pebbles cultivation can be carried out successfully both in the white plastic tube and in the bucket, with the latter it is recommended to locate the drainage holes on the side of the growing container (at 6 cm from the bottom of the bucket).